A 30 Mbps in-plane full-duplex light communication using a monolithic GaN photonic circuit. (7th June 2017) - Gao, Xumin; Yuan, Jialei; Yang, Yongchao; Li, Yuanhang; Yuan, Wei; Zhu, Guixia; Zhu, Hongbo; Feng, Meixin; Sun, Qian; Liu, Yuhuai; Wang, Yongjin
Abstract: We propose, fabricate and characterize photonic integration of a InGaN/GaN multiple-quantum-well light-emitting diode (MQW-LED), waveguide, ring resonator and InGaN/GaN MQW-photodiode on a single chip, in which the photonic circuit is suspended by the support beams. Both experimental observations and simulation results illustrate the manipulation of in-plane light coupling and propagation by the waveguide and the ring resonator. The monolithic photonic circuit forms an in-plane data communication system using visible light. When the two suspended InGaN/GaN MQW-diodes simultaneously serve as the transmitter and the receiver, an in-plane full-duplex light communication is experimentally demonstrated with a transmission rate of 30 Mbps, and the superimposed signals are extracted using the self-interference cancellation method. The suspended photonic circuit creates new possibilities for exploring the in-plane full-duplex light communication and manufacturing complex GaN-based monolithic photonic integrations.